A survey on teaching approaches of ten english language teachers in PKG Tengkawang zone / Adnan Harun - Harun, Adnan (2002)
The main reason of this research is to identify the most common teaching approaches practiced by the ESL Teachers in their Language teaching. The research involved 10 practicing ESL Teachers, 5 headmasters and 10 pupils from 5 schools in PKG (Pusat Kegiatan Guru) Tengkawang operational Zone. The focus of the research is to determine whether the teacher had practiced the approaches which were provided in their training as teacher trainees. From the research it is found that the teachers do not have a firm practice of any approaches.They are found to practice eclectic approaches by applying certain critena from each of the approach. The research also revealed that some of the approaches are failed to be applied due to certain constraints such as burden with clerical work, not enough funding for the materials and lack of knowledge of the teachers themselves. However, the teachers seemed to have done at least part of the criteria needed for the ESL teaching and they are willing to improve their way of teaching. The District Education Office should take into notice the requirement needed by the teachers for the betterment of the performance in the related Subject.